Stress-responses of microbial population and activity in activated sludge under long-term ciprofloxacin exposure. (1st March 2021) - Chen, Ya; Wang, Zhiping; Liu, Lili; Zhao, Hanbin; Wu, Pin
Abstract: In this study, the effects of ciprofloxacin on activated sludge were evaluated based on the microbial community and metabolic characteristics. The results indicated that the metabolism of chemical oxygen demand (COD) and nitrogen were inhibited with ciprofloxacin at mg/L level compared to the control experiment, and the concentration of ciprofloxacin was slightly decreased. High-throughput sequencing (HTS) results showed that ciprofloxacin greatly shaped the microbial communities in activated sludge, especially for the Nitrospirae phylum and Nitrospira genus. High concentrations of ciprofloxacin stimulated the enrichment of Zoogloea, thus reducing the stability of the activated sludge. Moreover, quinolone resistance proteins in Aeromonas were enriched, which demonstrates their competitive advantage in these enrichment incubations. Finally, the functional profiles were predicted through Tax4Fun, which revealed the adaption to microbes in activated sludge to the ciprofloxacin selective pressure. This work demonstrates the influence of ciprofloxacin on the activated sludge process, and can provide a useful reference for the assessment of the ecological security of ciprofloxacin. Graphical abstract: Image 1 Highlights: The microbial activity of activated sludge is inhibited by ciprofloxacin. The microbial community is shaped by the increase in ciprofloxacin content or exposure time. The nitrogen-metabolic microbes are inhibited by ciprofloxacin. Microbes enriched in ciprofloxacin medium may contain antibiotic resistance genes. Functional predictors indicate that microbes can adapt to the selective pressure of ciprofloxacin.